PO 120 - OUTCOMES EM CIRURGIA COLORRETAL. A PERSPETIVA DO DOENTE - Nogueira Pinto, Catarina; Inês Rebelo, Paula; Rodrigues Pereira, Cláudia; Leite Silva, Ana (Journal of the Portuguese Society of Anesthesiology, 2023)
x